Genome-wide identification of CAMTA gene family members in Medicago truncatula and their expression during root nodule symbiosis and hormone treatments - Yang, Yanjun; Sun, Tao; Xu, Luqin; Pi, Erxu; Wang, Sheng; Wang, Huizhong; Shen, Chenjia (Frontiers in Plant Science, 2015)
Calmodulin-binding transcription activators (CAMTAs) are well-characterized calmodulin-binding transcription factors in the plant kingdom. Previous work shows that CAMTAs play important roles in various biological processes including disease resistance, herbivore attack response and abiotic stress tolerance. However, studies that address the function of CAMTAs during the establishment of symbiosis between legumes and rhizobia are still lacking. This study undertook comprehensive identification and analysis of CAMTA genes using the latest updated M. truncatula genome. All the MtCAMTA genes were expressed in a tissues-specific manner and were responsive to environmental stress-related hormones. The expression profiling of MtCAMTA genes during the early phase of Sinorhizobium meliloti infection was also analyzed. Our data showed that the expression of most MtCAMTA genes was suppressed in roots by S. meliloti infection. The responsiveness of MtCAMTAs to S. meliloti infection indicated that they may function as calcium-regulated transcription factors in the early nodulation signaling pathway. In addition, bioinformatics analysis showed that CAMTA binding sites existed in the promoter regions of various early rhizobial infection response genes, suggesting possible MtCAMTAs-regulated downstream candidate genes during the early phase of S. meliloti infection. Taken together, these results provide basic information about MtCAMTAs in the model legume M. truncatula, and the involvement of MtCAMTAs in nodule organogenesis. This information furthers our understanding of MtCAMTA protein functions in M. truncatula and opens new avenues for continued research.